Appalachian State University Digitizing the Appalachian Consortium Press Publications : The Andrew W. Mellon Foundation Grant for the Humanities Open Book Program - Mitchem, Pamela Price (2018)
The Appalachian region of the United States is unique and diverse; and over the years, misunderstandings and stereotypes have evolved that fail to capture the richness of its diversity. Grants like the Humanities Open Book Program allow this richness to becomevisible and to be explored in greater depth -and by a wider range of people -than was possible before.The Appalachian State University Libraries holds the largest collection of works related to Appalachian Studies, including a complete collection of works published by the Appalachian Consortium Press (ACP). When the Consortium ceased operations, the archives, collections, and in some cases, the rights to the material were given to Appalachian State University. The Libraries applied for and received a two-year grant from The Andrew W. Mellon Foundation in 2016 to work in partnership with the UNC Press to digitize and reissue 73 works published by the Appalachian Consortium Press, considered founding and seminal works in the field. Sixty-nine of the works, containing monographs and conference proceedings, were added to Appalachian State University's Digital Collections, JSTOR and the Internet Archive, will soon be added to HathiTrust and will be harvested by DPLA. They are available freely on the website of the Libraries and print formats are distributed by the University of North Carolina Press.